Analysis of Computer Attitudes of Academic Staff in A Tertiary Institution - Haryanto, Sony; Sujianto (Journal Knowledge Industrial Engineering (JKIE), 2023)
This study investigates the factors influencing computer attitudes among lecturers at the National Institute of Technology Malang. Specifically, it examines the impact of gender, age, educational qualifications, length of teaching experience, personal computer ownership, participation in computer training, and computer usage skills. A descriptive research design was employed to explore relationships between these variables and test pre-formulated hypotheses. A sample of 100 lecturers was selected, and data were collected using a Likert Summarated Rating questionnaire. Descriptive statistical analysis and Multiple Linear Regression Analysis were used to analyze the data. The findings indicate a significant influence of computer skills on computer attitudes, with a regression coefficient (Î²) of 0.345, demonstrating a notable impact on computer user behavior. The statistical F test revealed a significant overall effect, with an F value of 4.138. The study also found a strong relationship between the variables, as indicated by the multiple correlation coefficient (R) of 0.489. The results suggest that computer expertise significantly affects computer attitudes, with a robust interrelation among the studied factors.